The Principle of Separation of Powers in Light of the Constitutional Amendment in 2016 Through the Relationship Between the Executive and the Legislative Branch - Benhamo, Tawes (Journal of Legal Studies and Researches, 2020)
The principle of separation of powers has an important standing for the Constitutionals, as it is considered as a criterion for classifying the political systems of States. It is a principle that aims to the lack of concentration of powers in the hands of a single body, but the Algerian political system of a special nature is based on the idea of dividing powers and functions under single leadership which is obvious through the dominance and interference of the executive in the jurisdiction of the legislature, as well as the means of influencing the executive on the legislative power, which is an idea contrary to the principle of separation of powers, that requires the independence of each power from the other with cooperation between them, although the Algerian constitutional founder doesn’t explicitly recognize this principle only in the constitutional amendment of 2016.